Analytical model of a composite girder with flexible adhesive bondline - Szeptyński, P. (Archives of Mechanics, 2024)
The paper presents a linear elastic one-dimensional Discrete Layer–Wise (DLW) analytical model of a composite girder consisting of two beams bonded together with a layer of a flexible adhesive. The model takes into account both longitudinal and transverse deformation of component beams, the First Order Shear Deformation Theory (FSDT) for these adherends as well as extensibility of the adhesive layer. A system of governing equations is derived and a general solution is found with the use of the method of generalized eigenvectors. Two examples are analyzed both with the use of the considered 1D analytical model and a 3D Finite Element Analysis (FEA) in order to validate predictions of the introduced theory. Satisfactory agreement is found between theoretical and numerical results.